Effect of grit-blasting air pressure on adhesion strength of resin to titanium. (March 2016) - Khan, Aftab Ahmed; Al Kheraif, Abdulaziz A.; Alhijji, Saleh Mohammed; Matinlinna, Jukka Pekka
Abstract: Aim: The objective of this laboratory study was to analyze the effect of different grit-blasting pressures on adhesion of resin to silica-coated and silanized Ti using the shear bond test. Materials and methods: A total of 24 commercially pure grade 2 Ti coupons (1 mm×20 mm×40 mm) were prepared and randomly assigned to 4 groups based on surface treatment: 150 kPa grit-blasting pressure with Rocatec TM Soft (group 1) for 10 s. Similarly, groups 2, 3 and 4 were treated at 280 kPa (control), 330 kPa and 380 kPa grit-blasting pressures, respectively, and followed by silanization. A total of 10 resin stubs per group were bonded onto each treated surface with photopolymerization. The shear bond strength was measured after 24 h dry storage in a desiccator, 2 months H2 O storage, and 4 months H2 O storage. Data were analyzed using descriptive statistics and two-way ANOVA ( p< 0.05). Results: After 24 h, initial SBS values of tested groups were significantly higher (32.0% for group 1, 39.1% for group 3, and 23.9% for group 4) than the control (group 2). After artificial aging, SBS values decreased in all the groups. The highest adhesion strength was seen in 150 kPa (13.0±3.0) and 280 kPa (4.9±2.4) after 2 months, and 4 months artificial aging, respectively. Conclusion: A lower grit-blasting pressure might promote adhesion strength in long term water aging.